A systematic review and meta-analysis of endocrine-related adverse events associated with interferon - Wang, Linghuan; Li, Binqi; Zhao, He; Wu, Peixin; Wu, Qingzhen; Chen, Kang; Mu, Yiming (Frontiers in Endocrinology, 2022)
Objectives To perform a systematic review and meta-analysis of interferon and endocrine side effects, including their incidence, evaluation, and management. Methods PubMed was searched through March 7th, 2021, by 2 authors independently (LH Wang and H Zhao). Early phase I/II, phase III experimental trials, prospective and retrospective observational studies were included. Stata 16.0 (StataCorp LLC, 16.0) was the main statistical software for meta-analysis. The weighted incidence and risk ratio were estimated for primary thyroid disease and diabetes mellitus. Results A total of 108 studies involving 46265 patients were included. Hypothyroidism was the most common thyroid disorder, followed by hyperthyroidism. IFN α+RBV treated patients experienced hypothyroidism in 7.8% (95%CI, 5.9-9.9), which was higher than IFN α (5.2%; 95%CI, 3.7-6.8) and IFN β (7.0%; 95%CI, 0.06-23.92). IFN α+RBV treated patients experienced hyperthyroidism in 5.0% (95%CI, 3.6-6.5), which was higher than IFN α (3.5%; 95%CI, 2.5-4.8) and IFN β (3.4%; 95%CI, 0.9-7.5). The summary estimated incidence of painless thyroiditis was 5.8% (95%CI, 2.8-9.8) for IFN α, and 3.5% (95%CI,1.9-5.5) for IFN α+RBV. The summary estimated incidence of diabetes was 1.4% (95%CI, 0.3-3.1) for IFN, 0.55% (95%CI, 0.05-1.57) for IFN α, 3.3% (95%CI,1.1-6.6) for IFN α+RBV. Conclusions Our meta-analysis shows a high incidence of endocrine adverse events provoked by IFN, further reinforced by combined RBV treatment. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022334131.